Crescimento econômico e restrição externa da economia brasileira: uma análise do padrão das exportações em relação ao BRIC e do Sistema de Inovação do Brasil (1980-2012) - Cardoso, Franciane Alves (2013)
This Master s Thesis aims to use the theoretical models of growth with restricted balance of payments, specifically Kaldor (1970) and Thirlwall (1979) models, to analyze the behavior and the pattern of specialization of Brazilian exports and imports in the last years. It is observed that, in some periods, the pattern of specialization has contributed in restricting long-term growth of the Brazilian economy. It has been hypothesized that overall this is due to lack of structural transformation policies. To achieve this goal, it analyzed the performance of Brazilian exports and imports disaggregating them according to their technological content. The basis for comparison was a group of countries to which Brazil is inserted in, the BRIC. In this regard, the work is a comparative analysis by using descriptive statistics. It is concluded that the low rate of GDP growth experienced by Brazil since the 1980s can be explained in part by the decoupling of the Brazilian National Innovation System (NIS) and the Brazilian productive structure. This would be reducing the income elasticity of exports and raising imports, causing a pattern of specialization intensive primary commodities and labor and low-skill labor